Process methods of pore structure and properties control of heat insulation ceramic construction materials - Щукіна, Людмила Павлівна; Цовма, Віталій Віталійович; Галушка, Ярослав Олегович; Міхеєнко, Лариса Олександрівна (Technology audit and production reserves, 2015)
The objects of study were ceramic materials obtained with the help of gas-forming additives. The work models various types of pore ceramic structure on the basis of non-sinterable clay and different pore-forming agents. Both inorganic (marl, dolomite), organic (sawdust, turf) and organic mineral (coal flotation tailings, ash slag) pore-forming additives were used with specified particle size. Such structural characteristics of ceramic materials were established as preferable pore size, all types of porosity, volume content of solid phase and structure anisotropy factor characterizing its uniformity degree. Structural parameters were studied in connection with type of pore-forming agent and properties of model samples which ensure better operational properties of materials. The highest mechanical strength was found in combined-type porous structures with tubular, globular and spherical pores in various combinations that were formed under usage of organic and organic mineral pore-forming agents. We observed a trend in materials to increase their strength with growth of closed porosity. Structure uniformity is found to improve with reduced pore-forming agent particle size, which makes the materials more strong and frost-resistant. Process parameters (type, quantity and particle size) of pore-forming agent were established enabling targeted formation of porous ceramics structure in order to improve the properties of heat insulation ceramic construction materials. The results represent the scientific interest for professionals working in the field of building materials, particularly in the field of production technologies of heat effective ceramics for energy-saving construction.